Modified Burch Colposuspension – analysis of the perioperative complications of first procedures - Wlaźlak, Edyta; Surkont, Grzegorz; Sobczuk, Anna; Stetkiewicz, Tomasz; Suzin, Jacek (Menopause Review/Przegląd Menopauzalny, 2005)
Increased awareness of the potential surgical complications may help in both appropriate preoperative patient assessment and decreasing complication rates. Perioperative complications of Burch colposuspension are mostly unpublished, and the incidence is probably higher than anticipated. Methods: This is a part of prospective randomized study planned to compare Burch colposuspension and tension free vaginal tape. Presented analysis refers to unification of operative technique of colposuspension. We analyzed perioperative complications of first 50 colposuspensions of two operators trained by prof. E. Petri from Germany. Results. Complications were as follows: urinary tract infection – 12%, haemorrhage >200 ml – 6.45%, haematoma – 2%, transient haematuria – 5%, bladder injury – urinary retention >1 day from catheter evacuation – 6%. We had no case of urinary retention >7 days from catheter evacuation, need of blood transfusion or ureteral kinking or injury. The incidence of bleeding complications, haematuria and urinary retention was becoming less frequent with the number of procedures. Conclusions: Proper operative technique of Burch colposuspension reduces the number of complications during first procedures. With the numbers of operations the incidence of complications is becoming less frequent.